"We Don't Do That Here": How Collaborative Editing with Mentors Improves Engagement in Social Q&A Communities - Ford Robinson, Denae; Lustig, Kristina; Banks, Jeremy; Parnin, Chris (In proceedings of the ACM Conference on Human Factors in Computing Systems (CHI), 2018)
Online question-and-answer (Q&A) communities like Stack Overflow have norms that are not obvious to novice users. Novices create and post programming questions without feedback, and the community enforces site norms through public downvoting and commenting. This can leave novices discouraged from further participation. We deployed a month long, just-in-time mentorship program to Stack Overflow in which we redirected novices in the process of asking a question to an on-site Help Room. There, novices received feedback on their question drafts from experienced Stack Overflow mentors. We present examples and discussion of various question improvements including: question context, code formatting, and wording that adheres to on-site cultural norms. We find that mentored questions are substantially improved over non-mentored questions, with average scores increasing by 50%. We provide design implications that challenge how socio-technical communities onboard novices across domains.